2005
DOI: 10.1002/hep.20824
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholestasis of Pregnancy and Bile Acid Levels *

Abstract: life-years than treatment according to "wait and see" strategy, depending on overall pancreatitis incidence (assumed to be 0.05%, 0.1%, 0.15%, or 0.2%/year) 3-5 and pancreatitis mortality (assumed to be 2.5%, 5%, 7.5%, or 10%). [6][7][8] In 6 of 16 possible scenarios, mortality during 10 years' follow-up proved to be reduced, but only in 4 of 16 possible scenarios life-years were gained by prophylactic cholecystectomy, because surgical death occurs early, whereas gained lives occur later. Further data on incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…They divided IHCP into mild (10-39 μmol/L) and severe ( 40 μmol/L) forms based on serum bile acids and found that there was a significant risk for fetal complications with serum bile acids greater than 40 μmol/L. Whether one can advocate changes in obstetric management based on serum bile acids in IHCP remains to be seen; however, this study supports the importance of monitoring serum bile acids in IHCP [11].…”
Section: Intrahepatic Cholestasis Of Pregnancysupporting
confidence: 66%
“…They divided IHCP into mild (10-39 μmol/L) and severe ( 40 μmol/L) forms based on serum bile acids and found that there was a significant risk for fetal complications with serum bile acids greater than 40 μmol/L. Whether one can advocate changes in obstetric management based on serum bile acids in IHCP remains to be seen; however, this study supports the importance of monitoring serum bile acids in IHCP [11].…”
Section: Intrahepatic Cholestasis Of Pregnancysupporting
confidence: 66%
“…Consequently, an active management has been suggested only for such patients which represent about 19% of the ICP pregnancies [1]. A wide discussion is now running on this topic and a randomised clinical trial to find the best perinatal management in ICP pregnancies with BA < 40 μmol/l is warranted [70,71].…”
Section: Obstetric Management and Pharmacological Treatmentmentioning
confidence: 97%
“…Malheureusement, il ne s'agit pas d'un test de routine (test hors nomenclature) et même pour un laboratoire spécialisé sa mesure n'est pas réalisée quotidiennement mais le plus souvent que deux fois par semaine. Ainsi, le praticien disposera des résultats avec un délai pouvant aller jusqu'à trois jours, période pendant laquelle les acides biliaires peuvent doubler [19][20][21][22]. Par ailleurs, les techniques de dosage actuellement disponibles ne donnent pas toujours des résultats parfaitement reproductibles.…”
Section: Examens Biologiquesunclassified